Obraz św. Hildegardy z Bingen w polskiej kulturze współczesnej - Tarnawska, Joanna (Załącznik Kulturoznawczy, 2023)
The article St. Hildegard of Bingen in Contemporary Culture was based on fragments of Licence Work.: St.Hildegard of Bingen – medival “feminist” and contemporary doctor of Church. The author concentrates on great interest of Saint Hildegard – the most interesting and best known monk of medieval ages. Saint Hildegard is a authority and inspiration for many different societes generating discussions. This work tries to answer questions on manipulation and use of Hildegard by contemporary culture. It also underlines stereotypes of thinking about medival ages and position of women in Church.